PERBANDINGAN PENUGASAN KELOMPOK DAN INDIVIDU TERHADAP HASIL BELAJAR PADA MATA KULIAH GENETIKA MAHASISWA PENDIDIKAN BIOLOGI SEMESTER 6B - Pipit Eka Fitriani; Regina Aulia Uriemanda; Resty Widiastuti; Iwan Ridwan Yusup; Milla Listiwati (Fakultas Keguruan dan Ilmu Pendidikan Universitas Pakuan, 2020)
COMPARISON OF GROUP AND INDIVIDUAL ASSIGNMENTS ON LEARNING OUTCOMES IN GENETIC COURSES OF BIOLOGY EDUCATION COLLEGE STUDENTSTo create a dynamic form in academic field, assignments are given by the lecturer within the process of the study. These assignments are given both to individuals and groups with different purposes. This research is aim to see the impacts of giving group assignments and individual assignments to student’s learning outcomes. The research method used was pre-experimental design research. The research subjects were students of biology education in semester 6 of 2014/2015 academic year. The results of the analysis show the average value of the group assignment is lower at 79.33 compared to the average value of the individual assignment of 80.22. Inferential analysis showed a significant group assignment value of 0.00 ˂ 0.05. Thus, we can conclude that the results of group assignments are significant compared to the results of individual assignments..